VENOUS ECTASIA OF THE VERMILION BORDER: COPPER VAPOR LASER TREATMENT - S. V. Klyuchareva; I. V. Ponomarev; Yu. N. Andrusenko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
We present the experience of application of "Yakhroma-Med" copper vapor laser system for the treatment of venouse ectasia (VE) of the vermilion border. The yellow wavelength of the generated laser radiation reaches 578 nm falls at the peak of hemoglobin absorption. The treatment was conducted in 58 patients with VE rising above the skin for no more than 1 mm. 100% clinical result. With a hemangioma size of up to 1 cm, treatment efficiency was 87% after the first procedure and complete resolution in 13% of the patients after the second procedure. At a size of more than 1 cm, the efficiency was 71% after the first procedure and 29% after the second. A 100% clinical result was obtained. The therapeutic effect persisted throughout the year in all 58 patients. It has been established that microcirculation disorders processes and further development of VE are affected by a variety of exogenous factors: about a half (48.3%) of the patients were deliberately subjected to excessive sunlight exposure, more than a quarter lived in regions with adverse climatic factors (wind, cold, abnormally low humidity, etc.) (27.6%), or regularly received hyperthermic procedures (steam bath, sauna, etc.) (25.9%). A burn (thermal, chemical) is found in the medical history of one in every five women (20.7%). 17.2% of the patients indulged in excessive consumption of condimental, spicy and hot food.